A novel hybrid modelling structure fabricated by using Takagi-Sugeno fuzzy to forecast HVAC systems energy demand in real-time for Basra city - Homod R.Z.; Togun H.; Abd H.J.; Sahari K.S.M. (Elsevier Ltd, 2023)
Climate control; Cooling systems; Differential equations; Energy management; Energy utilization; Forecasting; Fuzzy neural networks; HVAC; Nonlinear equations; Nonlinear systems; Real time systems; Uncertainty analysis; Climatic zone; Energy forecasting; Non-linear model; Outdoor thermal comfort; T-S fuzzy identifications; Uncertain disturbances; Fuzzy inference